Present Scenario of Circular RNAs (circRNAs) in Plants - Zhao, Wei; Chu, Shanshan; Jiao, Yongqing (Frontiers in Plant Science, 2019)
Circular RNAs (circRNAs) are new endogenous non-coding RNA family members that arise during pre-mRNA splicing in a reversed order in which the 3' and 5' ends are covalently closed. Compared to the comprehensive investigation of circRNAs in animals, circRNA research in plants is still in its infancy. Genome-wide identification and characterization of circRNAs have recently been performed in several plant species. CircRNAs are ubiquitously expressed and abundant in plants. The expression of circRNAs is often dependent on cell-type, tissue, and developmental stage, and it is particularly stress-inducible in plants. CircRNAs might play important roles in various biological processes in plants, including development and the response to biotic and abiotic stresses. Here, we review the current literature and provide a brief overview of circRNAs and their research status in plants, as well as the bioinformatic tools and database resources for circRNA analysis